In Vivo Comparison of Ultimate Tensile Strength of Nickel-Titanium Aligning Archwires Exposed to Fluoridated Mouthwash - Keerthana, Pasupureddi; Chitra, Prasad; S B, Puneeth; Janardhanam, LS Lokesh (Orthodontic Journal of Nepal, 2020)
Introduction: Orthodontists usually prescribe fluoridated mouthwash to their patients to mitigate risk of dental caries. These mouthwashes may alter the mechanical properties of archwires by dissolving the protective oxide-layer. The aim of the study was to examine the effects of fluoridated mouthwash on ultimate tensile strength of NiTi wires after three months of intra-oral use. Materials & Method: Sixty 0.014” (0.36mm) Nickel-titanium (NiTi) wires (Ormco Corp, Glendora, USA) were divided into three groups: Group A: as-received archwires serving as controls, Group B: intra-oral used wires exposed to placebo mouthwash and Group C: intra-oral used wires exposed to fluoridated mouthwash for a period of 3 months. Each wire was subjected to tensile testing using a table-top tensile testing apparatus. Ultimate tensile strength data was analysed with one-way analysis of variance (ANOVA) and Tukey testing at the 0.05 level of significance. Result: Results showed that amongst tested wires, those exposed to fluoridated mouthwash had least tensile strength (79.45 ± 1.33 N) as compared to wires exposed to placebo mouthwash (99.95 ± 0.91 N) and those in the control group (117.69 ± 0.66 N). The results were statistically significant at p <0.001. Conclusion: Ultimate tensile strength was least for wires exposed to fluoridated mouthwashes for a period of 3 months. Non-fluoridated mouthwashes can be used during the initial phase of leveling and aligning with NiTi wires.